USE OF COLEMANITE IN FERRONICKEL SMELTING - Keskinkiliç, Ender; Pournaderi, S.; Geveci, A.; Topkaya, Y. A. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Use of colemanite in metal-slag systems aims primarily to decrease the viscosity of slag and therefore to achieve better metal-slag separation. Enhanced metal-slag separation is helpful to decrease the number of suspended metal/alloy droplets in slag, i.e. the physical losses. In the literature, successful use of colemanite was reported both in steelmaking and copper matte smelting processes. Ferronickel smelting slags contain nickel in the range of 0.1-0.2% and correspondingly, metal-slag distribution ratio values of nickel are reported even above 200. On the contrary, nickel recoveries are hard to exceed 95%. This can be mostly attributed to the physical losses of nickel due to very high slag volume in ferronickel smelters; for 1 ton of ferronickel, 10-15 tonnes of slag are generated regardless of the type of the laterite, which contains significant quantity of gangue components. The authors thought that use of  colemanite could be a solution to decrease physical losses. Therefore, the use of colemanite in ferronickel smelting was investigated in the present work. Laboratory-scale smelting experiments were conducted using calcined and prereduced laterites in a vertical tube furnace under different gas atmospheres. The amount of colemanite added was in the range of 0 - 2.5% of the total charge. The experiments were also performed using ferronickel and slag samples obtained from a ferronickel smelter.